Motion/Performance Capture and The Afterlife of The Index. A Reconsideration of André Bazin’s “Myth of Total Cinema” - Grosoli, Marco (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2011)
The history of film technology is not a progressive and linear march towards the future : it is rather a discontinuous, irregular process where the past returns more often than not. Motion capture and performance capture technologies are particularly indicative examples of this dynamic, as their digital nature is far from opposed to the indexical bias of photography that (according to a widespread doxa) the digital is supposed to gradually supplant. On the contrary, they integrate the index in their own functioning. Moreover, some of the films making use of these devices (for instance Robert Zemeckis’s A Christmas Carol) seem to allegorize this very paradox. André Bazin has often been believed to advocate for a teleological view of history (and of the history of film technology) just because of his idealism. In fact, a close re-reading his writings, particularly of his “Myth of Total Cinema”, shows that his idealism works as an “antidote” against teleological presuppositions.